2010
DOI: 10.1007/s00441-010-1040-2
|View full text |Cite
|
Sign up to set email alerts
|

Resident macrophages in the cochlear blood-labyrinth barrier and their renewal via migration of bone-marrow-derived cells

Abstract: A large population of perivascular cells was found to be present in the area of the blood-labyrinth barrier in the stria vascularis of normal adult cochlea. The cells were identified as perivascular resident macrophages (PVMs), as they were positive for several macrophage surface molecules including F4/80, CD68, and CD11b. The macrophages, which were closely associated with microvessels and structurally intertwined with endothelial cells and pericytes, constitutively expressed scavenger receptor classes A(1) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
123
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(126 citation statements)
references
References 67 publications
3
123
0
Order By: Relevance
“…The cochlea could be a peripheral secondary target of systemic autoinflammation, but it is also plausible that autoinflammation is a local process originating within the inner ear. Recent studies have demonstrated that the mouse cochlea harbors cells that are immunoreactive with immune cell-specific markers under normal resting conditions (25)(26)(27), as well as in pathogenic disorders of hearing. In an Slc26a4-insufficient mouse model of hearing loss in human DFNB4 nonsyndromic deafness and Pendred syndrome, hearing loss is associated with an increase in staining of macrophage/ monocyte-like cells in the cochlea (28).…”
Section: Significancementioning
confidence: 99%
“…The cochlea could be a peripheral secondary target of systemic autoinflammation, but it is also plausible that autoinflammation is a local process originating within the inner ear. Recent studies have demonstrated that the mouse cochlea harbors cells that are immunoreactive with immune cell-specific markers under normal resting conditions (25)(26)(27), as well as in pathogenic disorders of hearing. In an Slc26a4-insufficient mouse model of hearing loss in human DFNB4 nonsyndromic deafness and Pendred syndrome, hearing loss is associated with an increase in staining of macrophage/ monocyte-like cells in the cochlea (28).…”
Section: Significancementioning
confidence: 99%
“…Others have applied histologic analyses focused on endothelial cells in fixed cochlear tissues of the stria vascularis to assess the integrity of blood-labyrinth barrier (Zhang et al 2012;Shi 2010). In vitro techniques using cell populations to mimic the vasculature of the inner ear, modeled after studies of the BBB, have been used to study the blood-perilymph barrier ).…”
Section: Figmentioning
confidence: 99%
“…In a recent study, we found that the intrastrial fluid-blood barrier also includes a large number of pericytes and perivascular-resident macrophage-like melanocytes (PVM/Ms) (12,13). The PVM/Ms are not observed in other capillary regions such as in capillary beds of the spiral ligament.…”
mentioning
confidence: 99%
“…The cell types of the intrastrial fluidblood barrier have yet to be characterized functionally, and the role of PVM/Ms in the intrastrial fluid-blood barrier is particularly elusive. In an earlier study (13), we characterized the PVM/ Ms as resident macrophages, because the cells are positive for several macrophage surface molecules, including F4/80, CD68, and CD11b. In this study, we further characterize the PVM/Ms as expressing several melanocyte markers.…”
mentioning
confidence: 99%